(untitled) (Tạp chí Y học Cộng đồng, 2026)
Objectives: The prevalence of overweight and obesity among university students is increasing, with physical inactivity being a key contributing factor. This study aimed to assess physical activity (PA) patterns among overweight and obese students at the University of Medicine and Pharmacy at Ho Chi Minh City, Vietnam. Methods: A cross-sectional study was conducted on 411 overweight and obese students using the World Health Organization’s Global Physical Activity Questionnaire (GPAQ). Data were entered using Microsoft Office Excel 2016 and analyzed in RStudio version 4.5.0. Results: A total of 50.9% of overweight and obese students did not meet the WHO’s recommendations on PA for health. The proportions of low, moderate, and high PA levels were 58.9%, 13.4%, and 27.7%, respectively. Male students engaged in more physical activity and were more likely to meet recommended PA levels than female students, who tended to engage in more sedentary behaviours (p < 0.05). A non-linear trend was found between PA levels and BMI categories. Conclusions: A large proportion of overweight and obese medical students did not meet the WHO physical activity recommendations. The findings indicate a need for medical universities to promote travel-related and recreational physical activity to support weight management.